Executives’ Perceptions of the Business Value of Information Technology: A Process-Oriented Approach - Tallon, Paul P.; Kraemer, Kenneth L.; Gurbaxani, Vijay (Journal of Management Information Systems, 2000)
:Despite significant progress in evaluating the productivity payoffs from information technology (IT), the inability of traditional firm-level economic analysis to account fully for the intangible impacts of IT has led to calls for a more inclusive and comprehensive approach to measuring IT business value. In response to this call, we develop a process-oriented model to assess the impacts of IT on critical business activities within the value chain. Our model incorporates corporate goals for IT and management practices as key determinants of realized IT payoffs. Using survey data from 304 business executives worldwide, we found that corporate goals for IT can be classified into one of four types: unfocused, operations focus, market focus, and dual focus. Our analysis confirms that these goals are useful indicators of payoffs from IT in that executives in firms with more focused goals for IT perceive greater payoffs from IT across the value chain. In addition, we found that management practices such as strategic alignment and IT investment evaluation contribute to higher perceived levels of IT business value.